STUDENTS' LEARNING INDEPENDENCE IN ISLAMIC RELIGIOUS EDUCATION LEARNING DURING THE COVID-19 PANDEMIC - Damayanti, Karlina; Arkanuddin, Aqil; Bintang, Muhammad Taufik (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2025)
Independence is one aspect of a person's nature, so in learning the concept of independence must be seen from the individual's own personality. Learning independence is the ability of students to realize their desires without depending on others. The purpose of this study is to find out the learning independence of students towards PAI learning during the covid-19 pandemic in grade VIII of SMPN 2 Teluk Jambe Timur. This research uses a survey method. Survey research is research that takes samples from one population and uses questionnaires as a data collection tool. covering 3 aspects: (1) awareness in participating in learning, (2) responsibility in doing assignments, (3) motivation in learning PAI, (4) video based learning methods. Data analysis was carried out using percentage analysis. students' learning independence in PAI subjects is considered good. Because in these 4 aspects, many respondents answered in agreement. With the results of this research, it can be said that students have been able to adapt to the current application of online learning. However, teachers must also always accompany students in the learning process so that students can better understand the material learned and can increase learning independence, especially in PAI subjects.